2016
DOI: 10.1002/oby.21418
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue natriuretic peptide receptor expression is related to insulin sensitivity in obesity and diabetes

Abstract: ObjectiveCardiac natriuretic peptides (NPs) bind to two receptors (NPRA‐mediator of signaling; NPRC‐clearance receptor) whose ratio, NPRR (NPRA/NPRC), determines the NP bioactivity. This study investigated the relationship of NP receptor gene expression in adipose tissue and muscle with obesity and glucose intolerance. Prospectively, the study also assessed whether changes in NP receptor expression and thermogenic gene markers accompanied improvements of insulin sensitivity.MethodsA cross‐sectional study of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 38 publications
7
75
0
Order By: Relevance
“…Little is known about the mechanisms responsible for the improvements in the NP-induced metabolic effects, but these may relate to NP secretion as well as NP receptor expression and post-receptor signalling. Indeed, in humans, whole-body insulin sensitivity was recently shown to strongly correlate with NPRA in subcutaneous AT (153) and skeletal muscle (124). In line with this, AT (148,153) and skeletal muscle (124) NPRC expression was negatively associated with whole-body insulin sensitivity.…”
Section: Natriuretic Peptide and Insulin Sensitivitymentioning
confidence: 62%
See 3 more Smart Citations
“…Little is known about the mechanisms responsible for the improvements in the NP-induced metabolic effects, but these may relate to NP secretion as well as NP receptor expression and post-receptor signalling. Indeed, in humans, whole-body insulin sensitivity was recently shown to strongly correlate with NPRA in subcutaneous AT (153) and skeletal muscle (124). In line with this, AT (148,153) and skeletal muscle (124) NPRC expression was negatively associated with whole-body insulin sensitivity.…”
Section: Natriuretic Peptide and Insulin Sensitivitymentioning
confidence: 62%
“…Indeed, in humans, whole-body insulin sensitivity was recently shown to strongly correlate with NPRA in subcutaneous AT (153) and skeletal muscle (124). In line with this, AT (148,153) and skeletal muscle (124) NPRC expression was negatively associated with whole-body insulin sensitivity. Additionally, NP degradation by NEP (74) may contribute to the development of IR (as was shown in obese Zucker rats) (184,185).…”
Section: Natriuretic Peptide and Insulin Sensitivitymentioning
confidence: 62%
See 2 more Smart Citations
“…Several studies suggested that adiponectin resistance might lead to elevated levels of adiponectin in patients with heart failure, which would in turn predict high CVD mortality. 48,49 In addition, the natriuretic peptide system including B-type natriuretic peptide (BNP) and the N-terminal fragment of its prohormone (NT-pro BNP) plays an important role in adipose tissue metabolism, 50,51 which might influence the secretion of adiponectin. Some studies demonstrated that NT-pro BNP and adiponectin had a significantly positive correlation and both could predict a high mortality in participants with chronic heart failure or chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%